2011
DOI: 10.1111/j.1462-2920.2011.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial biogeography of British soils

Abstract: Despite recognition of the importance of soil bacteria to terrestrial ecosystem functioning there is little consensus on the factors regulating belowground biodiversity. Here we present a multi-scale spatial assessment of soil bacterial community profiles across Great Britain (> 1000 soil cores), and show the first landscape scale map of bacterial distributions across a nation. Bacterial diversity and community dissimilarities, assessed using terminal restriction fragment length polymorphism, were most strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

84
554
11
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(652 citation statements)
references
References 60 publications
84
554
11
3
Order By: Relevance
“…We found evidence of links between plant traits and soil microbial communities despite the breadth of microbial functional groups included in our community fingerprints; the seemingly small effect sizes in our study are unsurprising, given the high microbial diversity and the potential influence of numerous soil physical and chemical properties. Soil pH in particular has an overriding effect on soil bacteria (Fierer, Bradford, & Jackson, 2007; Griffiths et al., 2011), and it is conceivable that some of the observed differences in bacterial community structure are a result of lower soil pH in the drought plots and deep microsites (Fridley et al., 2011) or a direct effect of differences in soil depth. Nevertheless, plant C:N ratios explained a greater proportion of the variation in soil bacteria compared to microsite characteristics (soil depth and pH) and the carbon construction costs of plant material explained an equivalent amount of variation in both bacterial and fungal community structures.…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of links between plant traits and soil microbial communities despite the breadth of microbial functional groups included in our community fingerprints; the seemingly small effect sizes in our study are unsurprising, given the high microbial diversity and the potential influence of numerous soil physical and chemical properties. Soil pH in particular has an overriding effect on soil bacteria (Fierer, Bradford, & Jackson, 2007; Griffiths et al., 2011), and it is conceivable that some of the observed differences in bacterial community structure are a result of lower soil pH in the drought plots and deep microsites (Fridley et al., 2011) or a direct effect of differences in soil depth. Nevertheless, plant C:N ratios explained a greater proportion of the variation in soil bacteria compared to microsite characteristics (soil depth and pH) and the carbon construction costs of plant material explained an equivalent amount of variation in both bacterial and fungal community structures.…”
Section: Discussionmentioning
confidence: 99%
“…0.02), even in large areas of contiguous habitats, suggesting that communities of both bacteria and macroorganisms are structured by analogous processes 31 . Recent microbial biogeography studies have revealed that the main environmental filters shaping spatial microbial diversity distribution are soil physico-chemical characteristics, land use and plant cover, whereas climatic and geomorphologic filters are less important 9,11,15,37 . Similar filters were also reported to explain soil bacterial community distribution in contrasted ecological regions at the scale of France 27,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of studies focusing on the driving factors of microbial distribution under a specific environmental gradient at regional or local scale, studies of microbial biogeography at large spatial scales have only been initiated recently (Fierer and Jackson, 2006;Drenovsky et al, 2010;Griffiths et al, 2011;Dequiedt et al, 2011). A notable example was the investigation of bacterial biogeography in British soil (Griffiths et al, 2011). Nevertheless, few of these studies have simultaneously considered climate, vegetation and soil properties as predictors of the microbial community structure.…”
Section: Introductionmentioning
confidence: 99%
“…Wakelin et al (2008) found that soil pH was the dominant driver of microbial community structure and function in a range of Australian agricultural soils. Despite the large number of studies focusing on the driving factors of microbial distribution under a specific environmental gradient at regional or local scale, studies of microbial biogeography at large spatial scales have only been initiated recently (Fierer and Jackson, 2006;Drenovsky et al, 2010;Griffiths et al, 2011;Dequiedt et al, 2011). A notable example was the investigation of bacterial biogeography in British soil (Griffiths et al, 2011).…”
Section: Introductionmentioning
confidence: 99%